2017
DOI: 10.3390/molecules22122255
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Sex-Biased Gene Expression and Putative Sex-Associated Genes in Eucommia ulmoides Oliver Using Comparative Transcriptome Analyses

Abstract: Eucommia ulmoides is a model representative of the dioecious plants with sex differentiation at initiation. Nevertheless, the genetic mechanisms of sexual dimorphism and sex determination in E. ulmoides remain poorly understood. In this study de novo transcriptome sequencing on Illumina platform generated >45 billion high-quality bases from fresh leaves of six male and female individuals of E. ulmoides. A total of 148,595 unigenes with an average length of 801 base-pairs (bp) were assembled. Through comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 88 publications
7
25
1
Order By: Relevance
“…In this study we found that the transition SNPs (34) were indeed more frequently detected than the transversion SNPs (6). Previous studies have reported a high level of nuclear genetic diversity at the population level of E. ulmoides [ 18 , 54 ]. In this study, we revealed that the frequency of plastid SNPs were 0.46 per kb at the whole cp genome level, lower than the average of 1.02 per kb in the nuclear genes of E. ulmoides [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we found that the transition SNPs (34) were indeed more frequently detected than the transversion SNPs (6). Previous studies have reported a high level of nuclear genetic diversity at the population level of E. ulmoides [ 18 , 54 ]. In this study, we revealed that the frequency of plastid SNPs were 0.46 per kb at the whole cp genome level, lower than the average of 1.02 per kb in the nuclear genes of E. ulmoides [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a high level of nuclear genetic diversity at the population level of E. ulmoides [ 18 , 54 ]. In this study, we revealed that the frequency of plastid SNPs were 0.46 per kb at the whole cp genome level, lower than the average of 1.02 per kb in the nuclear genes of E. ulmoides [ 54 ]. The difference of SNP frequency between the cp genome and the nuclear genes could be caused by insufficient sampling in this study and/or different variation rates between the plastid and nuclear sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonrecombining male-specific regions including many genes have also been characterized in C. papaya [28], P. trichocarpa [29], and S. latifolia [30]. Recently, one putative MADS box APETALA3-like gene, with male-biased expression, was identified to be probably involved in the sex determination in E. ulmoides based on transcriptomic analysis [31]. Nevertheless, to our knowledge, the sex determination mechanism in E. ulmoides is still in the dark to date.…”
Section: Introductionmentioning
confidence: 99%
“…One class of TFs is MADS-box, now known as the homeotic genes of ABCDE model for flower organ identification, which explains how the combination of different genes determines the identification of four flower organs. MADS-box genes regulate the early stage of flower development and help determine the characteristics of floral organs [48,49]. Some MADS-box genes were identified in the transcriptome data.…”
Section: Discussionmentioning
confidence: 99%